(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, it is necessary to develop the informational and analytical competence of future history teachers through the assimilation of the main scientific evidence of history from historical sources and manuals, and through historical-artistic works, through a more complete and deep understanding of its essence and importance.